PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PT WAP LOGISTIKINDO - Leonardo,; Tiurniari Purba, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The Effect of Service Quality and Promotion to the Customer Loyalty of PT WAP Logistikindo. This study is using methods both qualitatively and quantitatively with validity and reliability testing, multiple regression tests, correlation coefficient tests, partial correlation coefficient tests, t tests and F tests. The study result are: t test (partial test) Variables Service Quality For the Service Quality, the calculated obtained t value is 2,648 and the number of significance will be 0,009, this is less than the value a = 0.05 , Promotion Variable For Promotion variable, the calculated obtained t value is 11.022 and the number of significance is 0.000, this is less than the value a = 0.05 ,. F test (joint / simultaneous) calculation got the result of F Test by using the SPSS program to obtain a calculated value of F is 67.285. The obtained number of significance is 0,000, the value of significance was smaller than the number of a which is 0.05. Thus means that the independent variables which include Service Quality and Promotion simultaneously / simultaneously affect Customer Loyalty. Because the variable which is the Promotion variable has the highest partial correlation value that is equal to 11,022 compared to other variables, the variable, namely Promotion is the independent variable that predominantly impact the dependent variabe namely Customers Loyalty.